2011
DOI: 10.1348/147608310x520166
|View full text |Cite
|
Sign up to set email alerts
|

Rumination as a predictor of relapse in mindfulness‐based cognitive therapy for depression

Abstract: The results provide preliminary evidence that rumination is important in the process of depressive relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 22 publications
5
105
0
2
Order By: Relevance
“…56,57 Excessive selffocus in general is associated with negative affect 58 and self-focused rumination is associated with depression, 59-61 including depressive relapse. 62 With regard to the type of self-referential thinking, there is evidence that two general modes exist: narrative and experiential self-reference. Narrative selfreference is a concept of self that is extended in time and includes both memories of the past and intentions for the future.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…56,57 Excessive selffocus in general is associated with negative affect 58 and self-focused rumination is associated with depression, 59-61 including depressive relapse. 62 With regard to the type of self-referential thinking, there is evidence that two general modes exist: narrative and experiential self-reference. Narrative selfreference is a concept of self that is extended in time and includes both memories of the past and intentions for the future.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…This is relevant missing information, considering that training in mindfulness is supposed to reduce the risk of depressive relapse through the decrease of ruminative thinking (Williams & Kuyken, 2012). Moreover, post-treatment levels of rumination after a MBCT course were found to predict risk of relapse of major depressive disorder in the 12-month follow-up, after controlling for number of previous episodes and residual depressive symptoms (Michalak, Hölz, & Teismann, 2011). We also examined whether rumination mediates the relation between mindfulness skills and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, worry has been shown to predict poorer treatment response at post-treatment and 1-year follow up in individual and group cognitive behavior therapy (CBT) for social anxiety disorder (M€ ortberg & Andersson, 2014). Others have found that rumination is associated with delayed symptom remission in mild-moderately depressed participants (Jones, Siegle, & Thase, 2008) and greater likelihood of relapse following mindfulness based cognitive behavior therapy (Michalak, H€ olz, & Teismann, 2011). Such poor treatment response and lack of durable treatment effects associated with RNT have prompted the suggestion that RNT may be an endophenotype of treatment refractory patients who would benefit from personalized treatment (Mennin & Fresco, 2013).…”
mentioning
confidence: 99%